Analisis Kompetensi SDM dan Transformasi Digital terhadap Efektivitas Operasional Bank: Studi Literatur pada Lembaga Perbankan Nasional - Aulia Syahfitri; Hizhwati Husna; Maria Kristina; Nurul Azhizah; Hasyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of human resource (HR) competencies and digital transformation in improving operational effectiveness in national banking institutions. The research employs a literature review method by examining scientific journals, books, and official reports related to the research variables. The findings indicate that digital HR competencies, such as the ability to operate banking technology systems, data literacy, and adaptability to procedural changes, significantly contribute to enhancing the speed, accuracy, and quality of banking operational services. Furthermore, digital transformation, which involves the adoption of technologies such as digital banking, artificial intelligence, and process automation, can reduce operational costs, increase productivity, and strengthen internal control systems. These two variables are interdependent, where the success of digital transformation is highly influenced by the readiness and competencies of human resources as the main drivers of technology implementation. In conclusion, enhancing digital HR competencies and optimizing digital transformation are crucial factors in improving operational effectiveness, enabling banks to remain competitive in an increasingly digitalized financial industry.